Joint Risk of Rainfall and Storm Surges during Typhoons in a Coastal City of Haidian Island, China - Hongshi Xu (International Journal of Environmental Research and Public Health, 2018)
Public health risks from urban floods are a global concern. A typhoon is a devastating natural hazard that is often accompanied by heavy rainfall and high storm surges and causes serious floods in coastal cities. Affected by the same meteorological systems, typhoons, rainfall, and storm surges are three variables with significant correlations. In the study, the joint risk of rainfall and storm surges during typhoons was investigated based on principal component analysis, copula-based probability analysis, urban flood inundation model, and flood risk model methods. First, a typhoon was characterized by principal component analysis, integrating the maximum sustained wind (MSW), center pressure, and distance between the typhoon center and the study area. Following this, the Gumbel copula was selected as the best-fit copula function for the joint probability distribution of typhoons, rainfall, and storm surges. Finally, the impact of typhoons on the joint risk of rainfall and storm surges was investigated. The results indicate the following: (1) Typhoons can be well quantified by the principal component analysis method. (2) Ignoring the dependence between these flood drivers can inappropriately underestimate the flood risk in coastal regions. (3) The co-occurrence probability of rainfall and storm surges increases by at least 200% during typhoons. Therefore, coastal urban flood management should pay more attention to the joint impact of rainfall and storm surges on flood risk when a typhoon has occurred. (4) The expected annual damage is 0.82 million dollars when there is no typhoon, and it rises to 3.27 million dollars when typhoons have occurred. This indicates that typhoons greatly increase the flood risk in coastal zones. The obtained results may provide a scientific basis for urban flood risk assessment and management in the study area.